Driving the Morita–Baylis–Hillman Reaction to a Multicomponent Organic Transformation. Issue 4 (26th November 2013) - Guillouzic, Anne‐Françoise; Montel, Sonia; Laborde, Coralie; Volle, Jean‐Noël; Pirat, Jean‐Luc; Virieux, David
Abstract: The combination of a trivalent phosphorus reagent with an aldehyde and a Michael olefin in the presence of water led to the formation of functionalized phosphine oxides. This approach turned the Lewis base organocatalyzed Morita–Baylis–Hillman reaction into a multicomponent organic transformation to provide rapid access to polyfunctionalized molecules. Abstract : The combination of a trivalent phosphorus reagent with an aryl aldehyde and a Michael olefin in the presence of water led to the formation of functionalized phosphine oxides. This approach turned the Lewis base organocatalyzed Morita–Baylis–Hillman reaction into a multicomponent reaction to provide rapid access to polyfunctionalized molecules.